2020
DOI: 10.1155/2020/4620251
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Calea pinnatifida Inhibits Inflammation Induced by Carrageenan in a Murine Model of Pulmonary Neutrophilia

Abstract: Objective. The aim of this study was to investigate the anti-inflammatory effects of the crude extract (CE), derived fraction, and isolated compounds from Calea pinnatifida leaves in a mouse model of pulmonary neutrophilia. Methods. The CE and derived fractions, hexane, ethyl acetate, and methanol, were obtained from C. pinnatifida leaves. The compounds 3,5- and 4,5-di-O-E-caffeoylquinic acids were isolated from the EtOAc fraction using chromatography and were identified using infrared spectroscopic data and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…In view of previous reports that describe the potential anti-inflammatory properties of hydroxycinnamic acid derivatives [44], we also investigated the effects of chemical markers on NOx secretion. The results reinforce the potential of chlorogenic acid and its structural analogues (NCA; CCA) as anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…In view of previous reports that describe the potential anti-inflammatory properties of hydroxycinnamic acid derivatives [44], we also investigated the effects of chemical markers on NOx secretion. The results reinforce the potential of chlorogenic acid and its structural analogues (NCA; CCA) as anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors demonstrated that the low molecular weight carrageenan significantly reduces blood serum levels of TC, TG and LDL-C and improves the concentration of HDL-C in HFD fed mice, with a much stronger activity than that of high molecular weight carrageenan [50]. Furthermore, a considerable number of studies have shown that carrageenan causes inflammation [51][52][53], which should be fully considered in further studies, as this puts forward some limitations on the risk-free application of carrageenan. Although with certain side effects, further in-depth research on molecular mechanisms will help the development and utilization of Carrageenan.…”
Section: Carrageenanmentioning
confidence: 99%